Interstitial 1p32.1p32.3 deletion in a patient with multiple congenital anomalies. (10th June 2015) - Kehrer, Martin; Schäferhoff, Karin; Bonin, Michael; Jauch, Anna; Bevot, Andrea; Tzschach, Andreas
<x xml:space="preserve">Abstract</x> Interstitial deletions encompassing chromosome bands 1p32.1p32.3 are rare. Only nine unrelated patients with partially overlapping 1p32.1p32.3 deletions of variable size and position have been reported to date. We report on a 17‐month‐old boy with choanal atresia, hearing loss, urogenital anomalies, and microcephaly in whom an interstitial de novo deletion of 6.4 Mb was detected in 1p32.1p32.3 (genomic position chr1:54, 668, 618‐61, 113, 264 according to GRCh37/hg19). The deleted region harbors 31 RefSeq genes. Notable genes in the region are PCSK9, haploinsufficiency of which caused low LDL cholesterol plasma levels in the patient, and DAB1, which is a candidate gene for cognitive deficits, microcephaly, and cerebral abnormalities such as ventriculomegaly and agenesis of the corpus callosum. Choanal atresia, microcephaly, and severe hearing loss were previously not known to be associated with 1p32 deletions. Our reported patient thus broadens the spectrum of clinical findings in this chromosome region and further facilitates genotype‐phenotype correlations. Additional patients with overlapping deletions and/or point mutations in genes of this region need to be identified to elucidate the role of individual genes for the complex clinical manifestations. © 2015 Wiley Periodicals, Inc.